Using a dog's superior olfactory sensitivity to identify Clostridium difficile in stools and patients: proof of principle study. (13th December 2012) - Bomers, Marije K; van Agtmael, Michiel A; Luik, Hotsche; van Veen, Merk C; Vandenbroucke-Grauls, Christina M J E; Smulders, Yvo M
Abstract : Objective To investigate whether a dog's superior olfactory sensitivity can be used to detect Clostridium difficile in stool samples and hospital patients. Design Proof of principle study, using a case-control design. Setting Two large Dutch teaching hospitals. Participants A 2 year old beagle trained to identify the smell of C difficile and tested on 300 patients (30 with C difficile infection and 270 controls). Intervention The dog was guided along the wards by its trainer, who was blinded to the participants' infection status. Each detection round concerned 10 patients (one case and nine controls). The dog was trained to sit or lie down when C difficile was detected. Main outcome measures Sensitivity and specificity for detection of C difficile in stool samples and in patients. Results The dog's sensitivity and specificity for identifying C difficile in stool samples were both 100% (95% confidence interval 91% to 100%). During the detection rounds, the dog correctly identified 25 of the 30 cases (sensitivity 83%, 65% to 94%) and 265 of the 270 controls (specificity 98%, 95% to 99%). Conclusion A trained dog was able to detect C difficile with high estimated sensitivity and specificity, both in stool samples and in hospital patients infected with C difficile .